Molecular and biochemical studies on FCGRIA susceptibility in dengue infection / Zaiharina Mohamad Zamberi - Mohamad Zamberi, Zaiharina (2016)
Dengue, a mosquito-borne viral disease is a serious public health concern in many countries around the world. In Malaysia, suspected cases of dengue infection increase dramatically every year. Dengue infections cause a variable spectrum of manifestations ranging from dengue fever (DF) to dengue haemorrhagic fever (DHF) with plasma leakage that may lead to hypovolaemic shock, called dengue shock syndrome (DSS). Recent studies suggested the potential role of Fc gamma receptors (FCGRs) in the pathogenesis of dengue. The aim of this study was to determine the frequencies of copy number variation (CNV) of the FCGR1A gene and correlate the FCGR1A profile with its gene expression and serum protein level in dengue patients with vascular leakage and those without vascular leakage. Extracted DNA, RNA and serum were isolated from blood and use to quantify FCGR1A CNV, gene expression and protein concentration using quantitative real-time polymerase chain reaction (qPCR), reverse transcription-qPCR (RT-qPCR) and enzyme-linked immunosorbent assay (ELISA) respectively. One hundred dengue patients with signs of vascular leakage (case) and without vascular leakage (control), and 50 healthy subjects (normal) tested. Statistical analysis revealed that CNV of FCGR1A was significantly associated with dengue when compared to the normal controls. The circulating FcyRlA were also found to be significantly different between dengue patients and normal controls. However, there was no difference between dengue patients and normal controls, and dengue patients with vascular leakage and those without vascular leakage. These findings suggested that the FcyRlA plays a role in the susceptibility of dengue infection, however, showed no evidence in contributing to the severity of dengue. Although the correlation between these three experiments were not significantly related, the role of FCGR1A in vascular leakage should not be excluded. Further studies with larger sample size is needed to confirm this finding.